Strategic planning of hotel and restaurant business development - Столярчук, Валентина Николаевна (Technology audit and production reserves, 2014)
The possibility of long-term development of the hotel and restaurant industry is considered in the article. The purpose of research is the need to identify and address the reasons for the low competitiveness of the hotel and restaurant industry, consideration of the feasibility of its capacity planning and strategy development to achieve a leading position in the global market. The theoretical research methods (methods of analogy and extrapolation, system analysis, forecasting and innovative development of innovative planning) are applied. It is determined the low competitiveness of the hotel and restaurant industry due to its direction of innovation at meet the actual demand in the market. Attention to the need to consider the latent needs of consumers, their ability to extensive and intensive development is marked. It is proposed to take into account the phenomenon of convergence for the conquest of the leading positions in the world market development of strategic planning of the hotel and restaurant industry. The research results can be used by researchers and practitioners in the hotel and restaurant industry. The introduction of strategic planning of the hotel and restaurant industry will provide an opportunity to take a leading position in the market.